Position Paper of INoEA Working Group on Long-Gap Esophageal Atresia: For Better Care - van der Zee, David C.; Bagolan, Pietro; Faure, Christophe; Gottrand, Frederic; Jennings, Russell; Laberge, Jean-Martin; Martinez Ferro, Marcela Hernan; Parmentier, Benoît; Sfeir, Rony; Teague, Warwick (Frontiers in Pediatrics, 2017)
INoEA is the International Network of Esophageal Atresia and consists of a broad spectrum of pediatric specialties and patient societies. The working group on long gap esophageal atresia set out to develop guidelines regarding the definition of long gap esophageal atresia, the best diagnostic and treatment strategies, and highlight the necessity of experience and communication in the management of these challenging patients. Review of the literature and expert discussion concluded that long gap esophageal atresia should be defined as any esophageal atresia that has no intra-abdominal air, realizing that this defines esophageal atresia with no distal trachea-esophageal fistula. Long gap esophageal atresia is considerably more complex than esophageal atresia with distal tracheo-esophageal fistulas, and should be referred to a center of expertise. The first choice is to preserve the native esophagus and pursue primary repair, delayed primary anastomosis or traction/growth techniques to achieve anastomosis. A cervical esophagostomy should be avoided if possible. Only if primary anastomosis is not possible, replacement techniques should be used. Jejunal interposition is proposed as the best option among the major esophageal atresia centers. In light of the infrequent occurrence of long gap esophageal atresia and the technically demanding techniques involved to achieve esophageal continuity, it is strongly advised to develop regional or national centers of expertise for the management and follow-up of these very complex patients.